Desenvolvimento rural sustentável no Brasil: perspectivas a partir da integração de ações públicas e privadas com base na agroecologia - Assis, Renato Linhares de (Economia Aplicada, 2006)
This article aims to present an option for establishment of agroecological based sustainable rural development. Initially, an analysis is made of the process of diffusion of agroecological production systems in Brazil. Afterwards, the concept of sustainable development and possibilities of its accomplishment in relation to the difficulties brought by global economy is discussed. Following this, some questions are presented about public policy demands for the accomplishment of sustainable rural development, based at local action and related to agroecological production systems. Some premises and general recommendations are also presented for the accomplishment of this process. It is concluded that the execution of the proposal ideas only will be possible with enduring and integrated action of the different levels of action by public authorities, associated with real involvement of the society in the building of solutions.